Analisis Mashlahah Terhadap Putusan Mahkamah Konstitusi Nomor 22/PUU-XV/2017 - Wiwin Wiwin (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
This article discusses the Constitutional Court's Decision No. 22/PUU-XV/2017 which equalizes the age limit for marriage in Indonesia. The article employs a normative legal research method with a focus on legislation, analytical, conceptual, and maslahah approaches. The research findings indicate that Constitutional Court Decision No. 22/PUU-XV/2017 is based on philosophical, juridical, and sociological considerations, emphasizing the importance of equal age limits for marriage in Indonesia. Consequently, the phrase